Exploring the association with disease recurrence of miRNAs predictive of colorectal cancer. Issue 1 (March 2022) - Zanutto, Susanna; Ciniselli, Chiara Maura; Belfiore, Antonino; Dall'Olio, Valentina; Tizzoni, Laura; Varinelli, Luca; Pierotti, Marco Alessandro; Battaglia, Luigi; Verderio, Paolo; Guaglio, Marcello; Gariboldi, Manuela
Introduction: Disease recurrence after surgery is a crucial predictor of poor prognosis in colorectal cancer, where disseminated disease at the time of intervention can also be observed in localized early-stage cases. We evaluated the ability to predict disease recurrence of miRNAs from two signatures that we have found linked to the presence of colorectal cancer (CL signature) or adenoma (HgA signature) in higher-risk subjects. Methods: miRNAs from the signatures were studied longitudinally by quantitative real-time polymerase chain reaction in plasma from 24 patients with resectable colorectal cancer collected at the time of surgery and during scheduled follow-up across 36 months. Patients either showed relapse within 36 months (alive with disease (AWD)), or remained disease-free (no evidence of disease (NED)) for the same period. Results: Although the signatures did not predict recurrence, expression of the miRNAs from the CL signature decreased 1 year after surgery, and one miRNA of the signature, miR-378a-3p, almost reached significance in the NED subgroup (Wilcoxon signed-rank test: p -value = 0.078). Also, miR-335-5p from the HgA signature was higher in AWD patients before surgery (Kruskal–Wallis test: p -value = 0.019). Conclusions: These data, although from a small cohort of patients, support the possible use of miRNAs as non-invasive biomarkers in liquid biopsy-based tests to identify patients at risk of relapse and to monitor them during follow-up.